DEVELOPMENT OF A MYCOHERBICIDE FOR THE BIOLOGICAL CONTROL OF THE INVASIVE WEED “MIKANIA MICRANTHA” IN INDONESIAN NATIONAL PARKS. - Nguyen Minh Tu; Josefa Flores; Hans Peters (Yayasan Adra Karima Hubbi, 2025)
Mikania micrantha, an invasive weed, poses significant ecological threats in Indonesian national parks, outcompeting native vegetation and disrupting ecosystems. Traditional control methods, such as chemical herbicides, have proven inefficient and harmful to surrounding biodiversity. This study aimed to develop a fungal-based mycoherbicide to provide a sustainable, environmentally friendly solution for controlling Mikania micrantha. The research isolated and tested indigenous fungal strains for their mycoherbicidal properties against Mikania micrantha in two national parks: Bukit Barisan Selatan and Gunung Leuser. Field trials were conducted to assess the efficacy of the selected fungal strain on weed density and biomass reduction. The results demonstrated that the mycoherbicide significantly reduced Mikania micrantha density (54%) and biomass (60%) in treated quadrats compared to untreated controls. The treatment was more effective in wetter conditions, where fungal spore germination and plant infection were enhanced. These findings suggest that mycoherbicides can effectively control Mikania micrantha while minimizing the environmental impact of traditional herbicides. This study highlights the potential for fungal-based biocontrol methods as a viable tool in invasive species management. Further research is needed to evaluate the long-term effects and scalability of this mycoherbicide for broader applications in tropical ecosystems.